2014
DOI: 10.1080/02640414.2013.853132
|View full text |Cite
|
Sign up to set email alerts
|

The influence of 2 weeks of low-volume high-intensity interval training on health outcomes in adolescent boys

Abstract: The present study aimed to establish whether 2 weeks of high-intensity interval training would have a beneficial effect on aerobic fitness, fat oxidation, blood pressure and body mass index (BMI) in healthy adolescent boys. Ten adolescent boys (15.1 ± 0.3 years, 1.3 ± 0.2 years post-estimated peak height velocity) completed six sessions of Wingate-style high-intensity interval training over a 2-week period. The first session consisted of four sprints with training progressed to seven sprints in the final sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
5
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 49 publications
7
30
5
6
Order By: Relevance
“…This is in contrast to previous research which has shown similar or greater submaximal O 2 values following either HIIT or a traditional endurance-focused training programme (Baquet et al, 2002;McManus et al, 2005). It may be postulated that this finding, coupled with the elevated O 2 peak, demonstrates an enhanced exercise tolerance in the children who participated in the exercise intervention, similar to previous research (Barker et al, 2014;Sperlich et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This is in contrast to previous research which has shown similar or greater submaximal O 2 values following either HIIT or a traditional endurance-focused training programme (Baquet et al, 2002;McManus et al, 2005). It may be postulated that this finding, coupled with the elevated O 2 peak, demonstrates an enhanced exercise tolerance in the children who participated in the exercise intervention, similar to previous research (Barker et al, 2014;Sperlich et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…Although these findings are encouraging, previous studies have tended to prescribe exercise with a focus on cycling and running (Baquet et al, 2010;Barker, Day, Smith, Bond, & Williams, 2014;Lau et al, 2014;McManus, Cheng, Leung, Yung, & Macfarlane, 2005). However, Biddle, Gorley and Stensel (2004) have questioned the utility of structured activity programmes for children, suggesting that the provision of such programmes inadequately prepares children for the typically unstructured nature of adult activity.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…VO 2 max was obtained and verified breath-by-breath (Cortex Metalyzer III B, Leipzig, Germany) using a combined incremental-supramaximal treadmill protocol (Barker et al, 2014). Participants, with assistance from their parents/guardians, completed a health questionnaire before participation and were free of conditions, such as asthma, congenital heart disease and hypertension, amongst others that could alter autonomic and vascular functions.…”
Section: Participantsmentioning
confidence: 99%
“…The efficacy of a two week shock microcycle of HIIT to enhance cycling performance in young triathletes has been assessed using average power output (PO in watts) during a 20 min 44 . Whilst it can be argued that most young people rarely exercise at intensities that would elicit peak V O 2 , it has a strong empirical relationship with cardiometabolic health; therefore, the results from health-focused HIIT studies including MSFT will be included.…”
Section: Sport-specific Performance Outcomesmentioning
confidence: 99%